2016
DOI: 10.1515/acph-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of excipients on the stability and aerosol performance of salmon calcitonin dry powder inhalers prepared via the spray freeze drying process

Abstract: The effect of excipients on the stability and aerosol performance of salmon calcitonin dry powder inhalers prepared via the spray freeze drying processSpray freeze drying was developed to produce dry powders suitable for applications such as inhalation delivery. In the current study, the spray freeze drying technique was employed to produce inhalable salmon calcitonin microparticles. Effects of the carrier type, concentration of hydroxyl propyl-β-cyclodextrin and the presence of Tween 80 on the chemical and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In SFD, the liquid solution is sprayed into a vapor via a nozzle using a cryogenic fluid, such as liquid nitrogen [ 43 , 44 , 53 , 54 , 55 ]. The chemical composition, protein solution concentrations, atomization rate, freezing rate, as well as the temperature of cryogenic liquid have key roles in determining the density and particle size distribution of spray freeze-dried powders [ 50 ].…”
Section: Drying Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In SFD, the liquid solution is sprayed into a vapor via a nozzle using a cryogenic fluid, such as liquid nitrogen [ 43 , 44 , 53 , 54 , 55 ]. The chemical composition, protein solution concentrations, atomization rate, freezing rate, as well as the temperature of cryogenic liquid have key roles in determining the density and particle size distribution of spray freeze-dried powders [ 50 ].…”
Section: Drying Techniquesmentioning
confidence: 99%
“…Maa et al showed that SFD powders of influenza vaccines have superior stability compared with liquid formulations [ 58 ]. Processing other proteins such as rhDNase, anti-IgE monoclonal antibodies [ 21 ], calcitonin [ 53 ], and parathyroid hormone [ 44 ] using SFD provided stable dried powders with appropriate particle sizes and good flow properties.…”
Section: Drying Techniquesmentioning
confidence: 99%
“…Moreover, first-pass metabolism effect can be minimized by pulmonary delivery, which can be a good alternative delivery system for therapeutic peptides and proteins (Rytting et al 2008). The pulmonary delivery of therapeutic proteins and peptides, such as calcitonin (Poursina et al 2016), trastuzumab , and insulin (Exubera ® and Afrezza ® ) (Al-Tabakha 2015), have been investigated for the treatment of osteoporosis, breast cancer, and diabetes, respectively (Table 3). For systemic delivery through the pulmonary route, some specific physical barriers, such as blood proteolytic degradation, renal clearance, and hepatic first-pass metabolism, should be considered, and an effective dosage form of the drug is highly required to be absorbed through the alveolar and bronchial epithelium (Depreter et al 2013).…”
Section: Systemic Drug Deliverymentioning
confidence: 99%
“…After administration, drug distribution in the lung and retention in the appropriate site of the lung is important to achieve effective treatment (Labiris and Dolovich 2003a). A drug formulation designed for systemic delivery needs to be deposited in the lower parts of the lung to provide optimal bioavailability (Poursina et al 2016). However, for the local delivery of antibiotics for the treatment of pulmonary infection, prolonged drug retention in the lungs is required to achieve proper efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclodextrin is reportedly suitable for encapsulation of carotenoids (Madhavi & Kagan, 2008) in soft gels, providing higher bioavailability. 2-Hydroxypropyl-β-cyclodextrin (HPβCD) is an approved compound for inhalation, and researchers have confirmed that as a coating material, it increases the stability of the core compound (Poursina, Vatanara, Rouini, Gilani, & Rouholamini, 2016). Ungaro et al (2009) developed insulin aerosols using a double emulsion method.…”
Section: Introductionmentioning
confidence: 99%